2014
DOI: 10.18632/oncotarget.1954
|View full text |Cite
|
Sign up to set email alerts
|

Acrolein- and 4-Aminobiphenyl-DNA adducts in human bladder mucosa and tumor tissue and their mutagenicity in human urothelial cells

Abstract: Tobacco smoke (TS) is a major cause of human bladder cancer (BC). Two components in TS, 4-aminobiphenyl (4-ABP) and acrolein, which also are environmental contaminants, can cause bladder tumor in rat models. Their role in TS related BC has not been forthcoming. To establish the relationship between acrolein and 4-ABP exposure and BC, we analyzed acrolein-deoxyguanosine (dG) and 4-ABP-DNA adducts in normal human urothelial mucosa (NHUM) and bladder tumor tissues (BTT), and measured their mutagenicity in human u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
94
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(96 citation statements)
references
References 50 publications
1
94
0
1
Order By: Relevance
“…4-ABP can form a DNA adduct. In human liver tissue, higher 4-ABP-DNA levels were observed in HCC cases compared with controls [235][236][237][238][239][240][241] .…”
Section: -Aminobiphenylmentioning
confidence: 95%
“…4-ABP can form a DNA adduct. In human liver tissue, higher 4-ABP-DNA levels were observed in HCC cases compared with controls [235][236][237][238][239][240][241] .…”
Section: -Aminobiphenylmentioning
confidence: 95%
“…It is well known that aldehydes are highly reactive molecules that react with biomacromolecules (e.g. proteins, DNA) to yield covalent adducts, which are likely to cause a series of functional alteration of pathology [30, 31]. Existing evidences showed that aldehydes (such as formaldehyde, acetaldehyde, crotonaldehyde, furfural, acrolein, methoxyacetaldehyde, benzaldehyde and aldehydes intermediates of some drugs) could cause toxic side-effect and even increased cancer risk.…”
Section: Discussionmentioning
confidence: 99%
“…Human TCC is associated with residence in areas with higher industrial activity, and with environmental tobacco smoke exposure among non‐smokers . Both air pollution and tobacco smoke contain 4‐aminobiphenyl, arsenic, and acrolein, which are known bladder carcinogens . Exposure to high levels of phenoxyherbicides, arsenic contamination in well water, and chlorination by‐products in tap water are also linked to human TCC.…”
Section: Introductionmentioning
confidence: 99%